Seismic Shot Point Navigation Data from the Caribbean Sea and Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC1904 (1975) (IEDA: Marine-Geo Digital Library, 2007)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Robert D. Conrad expedition RC1904 conducted in 1975 (Chief Scientist: Dr. Manik Talwani). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Funding was provided by NSF grant: DES75-15865.